Adaptive Politeness and Hierarchical Negotiation: A Sociopragmatic Study of Bugis and Konjo Speech Communities in South Sulawesi - Alfridha Dwi Putri; Irfiani Bakri; Fisma Fisma (Hasanuddin University, 2025)
This study investigates the realization of adaptive politeness and hierarchical negotiation in the speech of Bugis and Konjo speakers in South Sulawesi, Indonesia. While politeness in Indonesian regional languages has often been described through hierarchical norms, this study demonstrates that politeness is better understood as an adaptive and relational process. Using a qualitative descriptive design with a sociopragmatic approach, natural conversations were collected from Bone and Bulukumba in 2023 through observation, recording, and semi-structured interviews. Data were analyzed using Culpeper (2021) pragmatic framework and Locher & Larina (2019) relational pragmatics model to identify linguistic markers of respect, empathy, and social harmony. The findings reveal that Bugis speakers maintain structured hierarchy through indirect and respectful forms that reflect the moral principle of siri’ na pacce, while Konjo speakers demonstrate greater flexibility through humor, familiarity, and contextual adaptation. Both groups exhibit adaptive politeness, balancing hierarchical awareness with social solidarity in everyday communication. These findings indicate that politeness in South Sulawesi is not a fixed linguistic system but a dynamic moral and pragmatic practice. The study contributes to the broader understanding of Southeast Asian pragmatics by showing how moral values and cultural identities are linguistically enacted in multilingual societies.